Development of Digital Banking Technologies in the Republic of Belarus - Zelenkevich, Marina; Korjenevskaya, Galina (Management and Administration Journal, 2019)
The purpose of the research is to determine the prospects and opportunities for digital transformation of the banking sector of the Republic of Belarus based on an analysis of the current state of bank informatization, current world trends to ensure a harmonious combination of interests of all participants in the country's banking system: the state, banks, firms and the public. The article analyzes the features of the current stage of development of the retail banking services market of the Republic of Belarus, which is characterized by dynamic development and widespread electronic and IT technologies. The expediency, necessity and timeliness of introducing such trend digital innovations of the retail banking sector of the Republic of Belarus as the development of the payment and settlement space, remote identification, including biometric, the development of the Open API, distributed registry technology (blockchain) are substantiated. Developed recommendations to improve the effectiveness of the proposed retail banking services through the modernization of existing and introduction of innovative ones. Identified key areas of innovation in the retail segment of banking services. Recommendations to improve the efficiency of retail banking services in the Republic of Belarus through the introduction of innovative digital banking technologies will enable Belarusian banks to gain strategic competitive advantages to achieve leadership positions in the financial market.